The biomechanics of the fastest sprinter with a unilateral transtibial amputation - Beck, O. N.; Grabowski, A. M. (Journal of Applied Physiology, 2018)
People have debated whether athletes with transtibial amputations should compete with nonamputees in track events despite insufficient information regarding how the use of running-specific prostheses (RSPs) affect athletic performance. Thus, we sought to quantify the spatiotemporal variables, ground reaction forces, and spring-mass mechanics of the fastest athlete with a unilateral transtibial amputation using an RSP to reveal how he adapts his biomechanics to achieve elite running speeds. Accordingly, we measured ground reaction forces during treadmill running trials spanning 2.87 to 11.55 m/s of the current male International Paralympic Committee T44 100- and 200-m world record holder. To achieve faster running speeds, the present study's athlete increased his affected leg (AL) step lengths (P < 0.001) through longer contact lengths (P < 0.001) and his unaffected leg (UL) step lengths (P < 0.001) through longer contact lengths (P < 0.001) and greater stance average vertical ground reaction forces (P < 0.001). At faster running speeds, step time decreased for both legs (P < 0.001) through shorter ground contact and aerial times (P < 0.001). Unlike athletes with unilateral transtibial amputations, this athlete maintained constant AL and UL stiffness across running speeds (P >= 0.569). Across speeds, AL step lengths were 8% longer (P < 0.001) despite 16% lower AL stance average vertical ground reaction forces compared with the UL (P < 0.001). The present study's athlete exhibited biomechanics that differed from those of athletes with bilateral and without transtibial amputations. Overall, we present the biomechanics of the fastest athlete with a unilateral transtibial amputation, providing insight into the functional abilities of athletes with transtibial amputations using running-specific prostheses. NEW & NOTEWORTHY The present study's athlete achieved the fastest treadmill running trial ever attained by an individual with a leg amputation (11.55 m/s). From 2.87 to 11.55 m/s, the present study's athlete maintained constant affected and unaffected leg stiffness, which is atypical for athletes with unilateral transtibial amputations. Furthermore, the asymmetric vertical ground reaction forces of athletes with unilateral transtibial amputations during running may be the result of leg length discrepancies.